Functional seed traits and germination patterns predict species coexistence in Northeast Mediterranean foredune communities. (22nd October 2020) - Del Vecchio, Silvia; Mattana, Efisio; Ulian, Tiziana; Buffa, Gabriella
Abstract: Background and Aims: The structure of plant communities, which is based on species abundance ratios, is closely linked to ecosystem functionality. Seed germination niche plays a major role in shaping plant communities, although it has often been neglected when explaining species coexistence. The aim of this work is to link the seed germination niche to community ecology, investigating how functional seed traits contribute to species coexistence. Methods: Species selection was based on a database of 504 vegetation surveys from the Veneto coast (Italy). Through cluster analysis we identified the foredune community and selected all of its 19 plant species. By using the 'Phi coefficient' and frequency values, species were pooled in different categories (foundation species, accidental species of the semi-fixed dune and aliens), then the 19 species were grouped according to their germination responses to temperature and photoperiod through cluster analyses. For each germination cluster, we investigated germination trends against temperature and photoperiod by using generalized linear mixed models. Key Results: We identified four germination strategies: (1) high germination under all tested conditions ('high-germinating'); (2) high germination at warm temperatures in the dark ('dark warm-cued'); (3) high germination at warm temperatures in the light ('light warm-cued'); and (4) low germination, regardless of conditions ('low-germinating'). Foredune foundation species showed a narrow germination niche, being 'low-germinating' or 'dark warm-cued'. Annual species of semi-fixed dunes were 'high-germinating', while alien species were the only members of the 'light warm-cued' cluster. Conclusions: Our research suggests that different categories of species have dissimilar seed germination niches, which contributes to explaining their coexistence. Climatic events, such as rising temperature, could alter germination patterns, favouring seed regeneration of certain categories (i.e. alien and semi-fixed dune species) at the expense of others (i.e. foundation species, pivotal to ecosystem functioning), and hence potentially altering the plant community structure.